The relationship between students’ attitudes and subjective norm on their intention to use mobile marketing services - Nor Farhany, Ahmad (2014)
This study was carried out to determine the relationships between attitudes, subjective norm on their intention to use mobile marketing. It is quantitative research with the use of random sampling method choose among polytechnic students. The result was analysed by the reliability analysis, factor analysis, Pearson coefficient correlation test and multiple regression analysis. Results of the research showed that attitude and subjective norm have a straight positive relationship with behavioural intention to use mobile marketing. However, when attitude and subjective norm influent by student experience, the relationship between attitude, subjective norm and behavioural intention become more significance. The suggested model can explain on the important factors determining the behavioural intention to use mobile marketing.